Toward Immersive Commerce: A Systematic Review of Augmented Reality Adoption in Retail - Maria Gracelina; Lisana Lisana (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
Augmented Reality (AR) has emerged as a prominent solution to address customer concerns in online shopping. This study aims to conduct a literature review on the factors influencing the adoption of AR in the retail industry. The reviewed literature spans the last five years, from 2020 to 2025, and was sourced from databases such as Scopus, Semantic Scholar, Web of Science, and Google Scholar. The PRISMA method was applied to facilitate the selection of relevant studies, resulting in a final dataset of 34 publications. The review identified 94 variables and 13 moderators commonly used in 11 prior studies. Among these, the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) were the most frequently applied frameworks. Research on AR adoption in retail has been conducted across various countries in Asia, Europe, and the Americas. This study is expected to provide insights beneficial for both researchers and retail practitioners in integrating AR technology into their business processes.